Comparative Performance of Lowland Hybrids and Inbred Rice Varieties in Nigeria - Akinwale, M.G.; Gregorio, G.; Nwilene, F.; Akinyele, B.O.; Ogunbayo, S.A.; Odiyi, A.C.; Shittu, A. (Science Alert, 2011)
The objective of this study was to compare the grain yield performance of lowland hybrids with that of some inbred varieties of rice in Nigeria with a view to identifying which of the two groups exhibits higher grain yield. Yield potential of 14 rice varieties comprising 10 commercial hybrids, 2 inbred varieties and 2 lowland NERICAs were evaluated at the Africa Rice Center, Ibadan Station during 2008 wet and 2009 dry seasons. The experiment was laid out in a randomized complete block design with three replications. Agronomic data were collected on days to 50% flowering, days to maturity, plant height, number of panicles per m2, panicle length, number of tillers per plant, panicle weight, number of grains per panicle, 1000 grain weight and grain yield. The number of panicles per m2, panicle weight and number of grains per panicle were significantly higher in the hybrids than in the inbred and interspecific varieties. The hybrids had the highest grain yield compared to the inbred and the interspecific lowland NERICA varieties. The results indicated that hybrids exhibited significant yield increase of 13.44% over the best lowland NERICAs and 15.17% over the best inbred variety WITA 4. The number of panicles per m2, panicle weight and number of grains per panicle appeared to be the main traits that contribute to higher grain yield in the hybrids. Therefore, the hybrids with the highest grain yield have huge potential in raising rice productivity in Nigeria